An Analysis of the Sentiment Classification of Short Messages Using Word2Vec - Lima, Raul de Araújo; Guerra, Paulo T. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2018.4436, 2018)
Sentiment analisys and the polarity classification of texts constitute one of the main tools currently used by companies and organizations for the most varied purposes. This work presents an analysis of the use of word embeddings, built through Word2Vec, in the process of features extraction for polarity classification of short messages written in English. The texts used were extracted from Twitter and the results obtained show that, in spite of the possible need to use larger textual bases to obtain better vectors, Word2Vec is a promising tool for the features extraction of textual data, contributing to obtain good classification results.